A novel bidirectional side exiting pledgetted suture for valve replacement surgery - Zheng, Junnan; Davies, Henry; Ni, Yiming (Frontiers in Surgery, 2022)
The pledgetted mattress suture is one of the most widely used suture techniques for valve replacement surgery. However, the traditional pledgetted suture has several defects including intertwining of the sutures and the pledget flipping over. Here we present a novel side exiting pledgetted suture that can overcome these defects. It offers cardiac surgeons a new alternative for valve replacement surgeries.